App-based learning as an alternative for instructors in teaching basic life support to school children: a randomized control trial. Issue 5 (3rd September 2019) - Doucet, Laurens; Lammens, Ruben; Hendrickx, Sarah; Dewolf, Phillipe
ABSTRACT: Background : The importance of early cardiopulmonary resuscitation (CPR) during an out-of-hospital cardiac arrest (OHCA) cannot be emphasized enough and has a major impact on survival. Unfortunately, CPR education in schools is often inadequate or non-existing due to lack of educators and financial resources. The introduction of application-based teaching could facilitate education as no instructor is needed. The aim of present study is to compare app-based self-teaching (intervention group) with a traditional instructor-led course (control group). This trial is in line with the endorsement of training school children by the World Health Organization (WHO). Methods : This randomized controlled trial contains 165 participants between 16 and 18 years. The control group followed an instructor-led course, while the intervention group used a tablet application to complete a self-education course.Both groups were taught in separated classes during 40 min and used manikins and automated external defibrillator (AED) trainer kits. Before and after training, both groups were evaluated in a practical test to examine their skills (an overall score and sub-scores on different sections were obtained, following ERC 2015 guidelines). Results : No significant difference ( p  = 0.304) in overall teaching effectiveness was found between both groups. Although, in a sub-analysis, we found significantly better results for the instructor group for checking airway ( p  = 0.018), asking for an AED ( p  < 0.01) and shocking the patient ( p  = 0.002). Conclusions : App-based teaching can be a valuable alternative for classic instructor-based education. Yet new apps have to be evaluated before being implemented in CPR education.